DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA MASA PANDEMI COVID-19 PERIODE TAHUN 2020-2021 - Susiyulianti, Tuti; Rukmini, Meme; Marwanto, I Gusti Gede Heru (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of four variables, namely asset structure, profitability (ROA & ROE), liquidity (CR & QR), and sales growth on capital structure. This type of research uses a quantitative research method. The population in this study used Manufacturing companies in the food and beverage subsector which were listed on the Indonesia Stock Exchange as many as 30 companies. The sampling technique in this study used a non-probability sampling technique with predetermined criteria and obtained a sample of 30 companies. The data analysis method used is descriptive statistical analysis, classical assumption test, and multiple linear analysis. Testing the hypothesis using the t-test and F-test. The research results obtained in this study show that Asset Structure has a significant negative effect on capital structure. Profitability (ROA) has no significant effect on capital structure. Profitability (ROE) has a significant positive effect on capital structure. Liquidity (CR) has a significant negative effect on capital structure. Liquidity (QR) has no significant effect on capital structure. Sales growth has no significant effect on capital structure. And, Asset Structure, Profitability (ROA & ROE), Liquidity (CR & QR), and Sales Distribution together influence the capital structure.